Analysis of biogas production potential based on livestock dung availability: A case of household biogas plants in Nepal. Issue 6 (24th May 2022) - Adhikari, Narayan Prasad; Adhikari, Ram Chandra
Abstract: This paper presents an analysis of the potential for household-scale biogas production based on cattle and buffalo dung in three geographical regions of Nepal. A field survey was conducted in 240 livestock-holding households, and data of daily fresh dung yield were obtained from 210 livestock individuals classified into four categories: mature buffalo (>3 year), young buffalo ( ≤ 3 year), mature cattle (>3 year) and young cattle ( ≤ 3 year). The data were collected in three different seasons with varying temperature and humidity. The energy values of the dung were experimentally measured. The results showed that the average daily dung yield per livestock in the monsoon was higher than that of the other seasons, for all geographical regions, because of higher fodder availability. Despite the highest livestock number per household in the mountains as compared to the hills and lowlands, the net availability of dung in the mountains was only about 30% of that of other two regions due to lower availability of fodder. Fodder availability, livestock herding hours, quality of dung and seasonal variations were found to be important parameters in determining the net potential biogas production. Based on these findings, measures to increase biogas production from available dung are discussed and generalized.